Socio-Political Conditions of the Abbasid Dynasty and Its Influence on Economic Development - Prastika, Yurika; Hidayati, Tri (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
Islamic civilization is a form of history that can be studied and studied, one of which was during the Abbasid Dynasty. This study aims to analyze and describe the socio-political conditions of the Abbasid Dynasty, and its influence on the economic development of various sectors. The research method in this study uses a historical approach and data analysis. The study results show that the good socio-political conditions of a nation and state have an important role in the economic development of the country and state. The results of this study show that very significant economic development occurred in the first period of the Abbasid Daulah, which increased in the agricultural, trade, and industrial sectors. In terms of economic institutions, the Abbasid Daulah prioritized three aspects, namely the state financial sector, taxation, and land ownership.